RETRACTED: The effect of personality traits on employees’ annual salaries in Chinese startups - Zhao, Longlong (Frontiers in Psychology, 2022)
Personality is a relatively regular habit of a person. It exerts a specific influence on personal behaviour and the corresponding results. At the same time, personality can provide a certain degree of explanation for the differences among individuals in behaviour and the related consequences. Economic differences are one of the discrepancies that exist among individuals. In order to explore the quantitative relationship between personality and individual income, this study takes 376 active employees of Chinese startups as the primary research objects. Additionally, considering the simplification and convenience of the survey, the annual salary investigated by this study is the pre-tax income of active startup employees. It uses quantitative methods to analyze the relationship between their personality traits and annual salary. Unlike the measures used in previous studies, this study employed the HEXACO-60 Inventory created by Ashton and Lee to investigate employees' personality traits. Compared to the Big Five model, HEXACO (Honesty-Humility, Emotionality, eXtraversion, Consciousness, Open to Experience, and Agreeableness) adds a new dimension to evaluate personality traits, called Honesty-Humility (H-H). H-H did not appear in previous studies related to personality and individual income. Therefore, there is no reference to the relationship between H-H and personal earnings. Considering that the content of H-H is highly consistent with the components of inter locus of control and the core spirit advocated by the Confucian culture, which influences Chinese people profoundly, this paper proposes a bold hypothesis, that is, H-H has a positive correlation with employees' annual salaries. Meanwhile, other corresponding hypotheses for the correlation between the other personality traits in HEXACO and employees' annual salaries are proposed. After that, the above hypotheses are tested with the help of correlation analysis. Then, the following conclusions can be quickly drawn. Consciousness, eXtraversion, Open to Experience, and Honesty-Humility positively correlate with employees' annual salaries. In comparison, Emotionality and Agreeableness negatively correlate with employees' annual salaries.